Did China diversify its foreign reserves?. (4th October 2011) - Sheng, Liugang
SUMMARY This paper takes a novel approach to detect the latent currency portfolio of Chinese foreign exchange reserves and the underlying portfolio management strategies during 2000 and 2007. Based on a portfolio accounting identity and the budget constraint of the Chinese central bank's holding of foreign assets, the monthly growth rate of reserves can be decomposed into monthly rate of return, valuation effects of exchange rates, and monthly net purchase rate. The valuation effect reveals the value share of each currency. Bayesian inference is adopted to estimate the state‐space model with a mixture of Gaussian distributions. The results show that China significantly and dramatically diversified its reserves out of the US dollar in 2002: both the euro's value and quantity shares increased from 5% to more than 20%. By the end of 2007, China held about (at most) 67.3% of its reserves in the US dollar, 22% in the euro, 2.5% in the Japanese yen, 4.7% in the Australian dollar, and 3.5% in the British pound. The average annual rate of return was about 3%. Copyright © 2011 John Wiley & Sons, Ltd.